Nemi liki - Leskovšek, Nika (Amfiteater (Ljubljana), 2023)
The paper begins by analysing the ideas, themes and motifs of the theatre texts from the anthology The Generator:: for Manufacturing Any Number of Drama Complexes (Slovenian Experimental Dramatic and Performative Texts from the Modernist Period (1966–1986)). It aims to shed light on the anthology’s selected texts through the female perspective, or rather, its absence. It deals with the consequences that the absence of awareness about the lack of a female perspective in Slovenian drama can have on the representation of women and woman(liness). The paper explores such representations in Slovenian (exper- imental) drama and raises awareness about the possible effects of patriarchal ideology and its consequences by analysing the plays’ ideas, themes and motifs. In doing so, it pays special attention to the difference between men’s and (rare) women’s playwriting. The texts from The Generator are taken merely as a case study to indicate the presence of particular symptoms in Slovenian (experimental) drama within the anthology’s given period. The paper briefly highlights the differences in the representation of woman(liness) from a broader developmental perspective, from a temporal distance, in the form of a comparative analysis of contemporary women’s playwriting, specifically, Simona Hamer’s 2010 play Nemi lik (The Silent Character).
Keywords: dramatičarke; eksperiment; experiment; female playwrights; modernism; modernizem; representation of women; reprezentacija žensk; Slovenian drama; slovenska dramatika; womanliness; women's writing; ženska pisava; ženskost